Hydatid cyst within a choledochal cyst - Ruchirendu Sarkar; Ram Mohan Shukla; Sujay Maitra; Malay Bhattacharya; Biswanath Mukhopadhyay (Wolters Kluwer Medknow Publications, 2013)
A 5 year 4 months old male child presenting with pain abdomen and jaundice was diagnosed to have type 1 choledochal cyst on ultrasonography and magnetic resonance cholangio pancreatography. On exploration, the cystic dilatation of common bile duct was found to have a hydatid cyst (HC) inside it. The per-operative findings were confirmed by histopathology. Association of HC within a choledochal cyst is extremely rare and has been reported only twice before in the available English literature.